Pengaruh Jenis Mulsa dan Konsentrasi Pupuk Organik Cair terhadap Pertumbuhan dan Hasil Tanaman Cabai Besar (Capsicum Annum L.) - IDO RODO SIMANJUNTAK; I NYOMAN RAI; I MADE SUKEWIJAYA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2023)
The Effect of Mulch and Liquid Organic Fertilizer on Growth and Production of Red Chilli (Capsicum annuum L.) Chilli (Capsicum annuum L.) is one type of vegetable plant that has high economic value and high demand in Indonesia. Organic mulch treatment and liquid organic fertilizer are among the organic farming techniques could be used to increase the production of red chilli. The aim of the study was to find the type of organic mulch and concentration of liquid organic fertilizer Agrobost to increase the production of red chilli. The research used a randomized group with split plot design in separate plots with two treatment factors. The first factor was mulch treatment consisting of 3 levels, i.e. without mulch, husk charcoal mulch, and saw shaved mulch. The second factor was the concentration of liquid organic fertilizer with 3 levels of treatment, i.e. without giving liquid organic fertilizer, giving liquid organic fertilizer at concentration of 7.5 mL/L of water, and 15 mL/L of water. The results showed that there was no interaction between mulch treatment and liquid organic fertilizer on the growth and yield of large red chilli plants. Giving husk charcoal mulch could increase the relative water content of leaves, number of fruit formed, and suppress weed populations. Liquid organic fertilizer with a concentration of 15 mL/L of water could increase plant height, leaf chlorophyll content, and leaf relative water content.